The effect of special mental exercises to develop the accuracy of the performance of some basic skills for youth futsal players - Hammad, Salah Hadi; Abdulrahman, Mohammed Abdulqader; Najim, Layth Mustafa (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to add mental exercises in the training curriculum and to identify their impact on thevariables of the research under study. The experimental design on a sample of (18) players were distributed totwo experimental and control groups equally. The development of the skills under study, and therecommendations of the adoption of mental exercises in the stage of special preparation in the trainingcurricula for young people by trainers.